2018
DOI: 10.1109/jstsp.2018.2824980
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum Sharing Backhaul Satellite-Terrestrial Systems via Analog Beamforming

Abstract: Abstract-Current satellite and terrestrial backhaul systems are deployed in disjoint frequency bands. This fact precludes an efficient use of the spectrum and limits the evolution of wireless backhauling networks. In this paper, we propose an interference mitigation technique in order to allow the spectrum coexistence between satellite and terrestrial backhaul links. This interference reliever is implemented at the terrestrial backhaul nodes which are assumed to be equipped with multiple antennas. Due to the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…In the spectrum sharing between satellite communications and terrestrial communications, some of the schemes work in the overlay mode [8], [9]. When operating in this mode, terrestrial users are often cognitive users, satellite users are often primary users, and both use the same frequencies.…”
Section: A Background and Motivationsmentioning
confidence: 99%
“…In the spectrum sharing between satellite communications and terrestrial communications, some of the schemes work in the overlay mode [8], [9]. When operating in this mode, terrestrial users are often cognitive users, satellite users are often primary users, and both use the same frequencies.…”
Section: A Background and Motivationsmentioning
confidence: 99%
“…One spectrum coexistence scenario between fixed satellite service (FSS) system and terrestrial cognitive radio system shown in Fig. 1 is considered in this paper, where the FSS system acts as the primary network and shares the spectrum resource with the terrestrial secondary network [13]- [15]. In the considered scenario, the FSS system consists of a geosynchronous (GEO) satellite S and one earth station E located in the center of a circular area with radius l, and M CBSs of the secondary network follow uniform distribution in this circular area.…”
Section: System Modelmentioning
confidence: 99%
“…3GPP, ITU, ETSI) and researchers have recently been focused on the extension of the cognitive radio concept to satellite-terrestrial networks [7]- [9]. At present, a tremendous amount of effort has been made to explore a new network architecture that allows satellite networks to coexist with terrestrial networks in the same frequency band through CR techniques [10]- [15]. As a result, the cognitive satellite-terrestrial networks (CSTNs) with high spectrum efficiency have been proposed as a promising solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concretely, we propose a variation of FPP-SCA in [8]. For more details, the reader can refer to [11]. When an hybrid analogdigital beamforming design is targeted, the optimization problem shall be reconsidered.…”
Section: Optimization Problemmentioning
confidence: 99%